2021
DOI: 10.1007/s12094-021-02623-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemotherapy-induced nausea and vomiting in the real-world setting in Spain

Abstract: Purpose Proper monitoring and management of chemotherapy-induced nausea and vomiting (CINV) with antiemetics is crucial for cancer patients. This study aimed to evaluate the use of antiemetics for the treatment of highly emetogenic chemotherapy (HEC) including carboplatin in the real-world setting in Spain. Methods A representative panel of cancer specialists was asked to collect information about the antiemetic treatments provided to patients receiving ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Poor adherence to recommended prophylaxis has been reported, in several observational studies [4][5][6]17]. Suboptimal adherence to prophylaxis may lead to uncontrolled CINV [28] with significant impact not only on patient's quality of life but also on CINV-related direct costs such as acquisition cost of antiemetic drugs and rescue medication, administration devices, add-on treatments, nursing and physician time, unscheduled office visits, emergency room admissions and, in some cases, extended hospitalization or readmission [25,35,41]; this leads to an increased economic burden to healthcare systems, as shown in various international studies.…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to recommended prophylaxis has been reported, in several observational studies [4][5][6]17]. Suboptimal adherence to prophylaxis may lead to uncontrolled CINV [28] with significant impact not only on patient's quality of life but also on CINV-related direct costs such as acquisition cost of antiemetic drugs and rescue medication, administration devices, add-on treatments, nursing and physician time, unscheduled office visits, emergency room admissions and, in some cases, extended hospitalization or readmission [25,35,41]; this leads to an increased economic burden to healthcare systems, as shown in various international studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, implementation of those recommendations has been reported to be inadequate worldwide 10 12–1510 and Europe 13 16. In contrast, two nationwide surveys11 17 on the use of prophylactic antiemetics for patients receiving HEC in Japan have shown that the recommended three-drug combination (serotonin-3 receptor antagonist (5HT 3 RA), dexamethasone (Dex) and neurokinin-1 receptor antagonist (NK 1 RA)) was administered in approximately 60% and 74% of patients, respectively, within 3 years of the guidelines’ publication in 2010, suggesting widespread use of appropriate antiemetic therapy.…”
Section: Introductionmentioning
confidence: 99%